Analisa Perancangan Kampung Vertikal pada Kawasan Kumuh Kampung Aur Kota Medan - Wildan, Ahmad; Fitri, Rahmadhani (Jurnal Teknik dan Teknologi Indonesia, 2024)
Kampung Aur, situated along the banks of the Deli River in Medan, is a densely populated informal settlement characterized by environmental degradation and urban blight. To mitigate slum expansion, this study proposes a habitable vertical housing design that preserves local socio-cultural values through the ‘vertical kampung’ concept. Integrating green open spaces and efficient wastewater treatment system, this vertical model rejuvenates the urban fabric while maintaining community social cohesion. This research employs survey methods, field observations, literature reviews, and site analyses, utilizing a tropical architecture framework to address high-density residential challenges along the Deli River basin.